KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA SEBAGAI INOVASI MENGHADAPI REVOLUSI INDUSTRI 4.0 - Khairatunnisa Khairatunnisa (Universitas Muria Kudus, 2023)
The purpose of this study is to discuss the implementation of an autonomous curriculum in language learning as an innovation in facing the Fourth Industrial Revolution.The research method used is online literature review. This research is descriptive qualitative because it takes the form of disclosing facts that are already known, which focuses on disclosing a problem and current situation. Triangulation is used as a data collection method, inductive reasoning is used in data analysis, and meaning rather than generalization is emphasized in qualitative research findings.The results of the study found that First, the industrial revolution 4.0 was formed by technological disruptions that changed needs in the education sector. This has triggered the need to update the 2013 curriculum given the progress and demands of the 21st century. One form of streamlining the 2013 curriculum is an autonomous curriculum. structure for learning recovery. Third, the use of ICT in education will enable independent curriculum integration in language acquisition to address issues of the fourth industrial revolution. Several types of information technology, including e-books, email, and social media, can be included in language learning.